Communication Development People in the Revolutionary Era Industry 4.0 & Covid-19 - Muhammad Rizal Akbar; Dawami; Windayani (Linguanusa : Social Humanities, Education and Linguistic, 2023)
Introduction to The Problem: The existence of the Covid-19 pandemic caused the government to implement various policies, these policies were relevant to the Industrial revolution 4.0, which in this era was the main characteristic of information systems in software, in this era the main objects were humans and technology. Purpose: Therefore this research aims to discuss the development of human communication in facing the era of the industrial revolution 4.0 and Covid-19. Design/methods/approach: This research is a document or library study. data collected through documentation. Literature review method through literature relevant to research. Then the data were analyzed using content analysis based on the theme. Findings: The results of the study show that in the face of the industrial revolution era, human communication development can be done by improving communication, improving digital skills. Research implications/limitations: This study recommends that the next researcher further develop research, especially in the type of research, research subjects and data analysis techniques. Originality/value: this research provides new information about communication in the era of the industrial revolution 4.0 about how communication was formed during Covid- 19.